2016
DOI: 10.7717/peerj.2136
|View full text |Cite
|
Sign up to set email alerts
|

Simple approach for ranking structure determining residues

Abstract: Mutating residues has been a common task in order to study structural properties of the protein of interest. Here, we propose and validate a simple method that allows the identification of structural determinants; i.e., residues essential for preservation of the stability of global structure, regardless of the protein topology. This method evaluates all of the residues in a 3D structure of a given globular protein by ranking them according to their connectivity and movement restrictions without topology constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…This single mutant, named 6a-R25G, showed a significant lower thermodynamic stability and enhanced fibrillogenic properties [11]. Other reports have shown that single point mutations incorporated in other segments of 6aJL2 (such as Phe2Ser, Phe2Pro, Phe2Ala, Phe2Leu, Phe2Trp, Gln6Asn, Pro7-Ser, His8Ser, Arg25Gly, Arg25His, Ile30Gly, and Tyr36Phe) generated variants that decreased thermodynamic stability [13][14][15][16].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This single mutant, named 6a-R25G, showed a significant lower thermodynamic stability and enhanced fibrillogenic properties [11]. Other reports have shown that single point mutations incorporated in other segments of 6aJL2 (such as Phe2Ser, Phe2Pro, Phe2Ala, Phe2Leu, Phe2Trp, Gln6Asn, Pro7-Ser, His8Ser, Arg25Gly, Arg25His, Ile30Gly, and Tyr36Phe) generated variants that decreased thermodynamic stability [13][14][15][16].…”
Section: Introductionmentioning
confidence: 88%
“…somatic hypermutation, several hot spots stand along their encoding DNA sequence. Other reports have shown that single point mutations incorporated in other segments of 6aJL2 (such as Phe2Ser, Phe2Pro, Phe2Ala, Phe2Leu, Phe2Trp, Gln6Asn, Pro7-Ser, His8Ser, Arg25Gly, Arg25His, Ile30Gly, and Tyr36Phe) generated variants that decreased thermodynamic stability [13][14][15][16]. Although germ lines can be identified as kappa (j) or lambda (k) with expression levels in humans of 60% and 40%, respectively [9], it is striking that k V L s encoded by germ lines 6a and 3r are highly susceptible to amyloid aggregation [10].…”
Section: Introductionmentioning
confidence: 99%
“…That is why there are multiple proposals to increase their structural resistance at high temperatures ( Gao et al, 2016 ; Kumar et al, 2016 ; Kean et al, 2017 ). An example is the hydrophobic packaging where the amino acid residues are oriented toward the protein core, being the main stability factors ( Reed et al, 2013 ; Luna-Martínez et al, 2016 ); It should be mentioned that studies on directed mutations carried out for the filling of hydrophobic cavities have resulted in an improvement of stability by hydrophobic packaging ( Christensen and Kepp, 2013a ; Oda and Kinoshita, 2015 ). Likewise, electrostatic interactions that occur between amino acids of opposite charge, also have great importance to maintain the stability of the conformation of the protein ( Sohini and Srikanta, 2009 ; Christensen and Kepp, 2013a ).…”
Section: Introductionmentioning
confidence: 99%